FEATURES OF THE PNEUMATIC SEEDER AND ITS ROLE AT THE PRESENT TIME - Temirkulova Nargiza Maminjanovna (Bright Mind Publishing, 2025)
The precision seeding machine is a high-tech solution for high-precision seeding, which implements a seed-by-seed distribution system.
Keywords: Soil moisture, hardness, density, machine quality, productivity and energy intensity, crucial agricultural tools.